Mediating roles of meaning in life and psychological flexibility in the relationships between occupational stress and job satisfaction, job performance, and psychological distress in teachers - Yildirim, Murat; Dilekçi, Ümit; Manap, Abdullah (Frontiers in Psychology, 2024)
Employees may experience stress in the workplace for various reasons. Psychological strengths may help them to cope with emerging challenges and foster mental health and work productivity. This study examined the mediating roles of meaning in life and psychological flexibility in the relationships between perceived occupational stress and job satisfaction, job performance and psychological distress. This cross-section study included 554 teachers (56.0% males; Mage = 36.99 ± 7.88 years) at all school levels in Türkiye. The research data was collected through a convenience sampling method using an online survey. Participants completed self-report measures of meaning in life, psychological flexibility, perceived occupational stress, job satisfaction, job performance, and psychological distress. Pearson product–moment correlation and parallel mediation model using PROCESS macro (Model 4) were utilized to analyze the data. The results showed that perceived occupational stress had a significant effect on meaning in life, psychological flexibility, job satisfaction, job performance, and psychological distress. Also, meaning in life and psychological flexibility had significant effects on job satisfaction, job performance, and psychological distress. Furthermore, meaning in life and psychological flexibility partially mediated the relationships between occupational stress and job satisfaction, job performance, and psychological distress. These findings highlight the significance of considering meaning in life and psychological flexibility as crucial factors in mitigating the impact of occupational stress on employee mental health and work productivity. By focusing on enhancing employees’ sense of meaning and their ability to adapt flexibly to workplace challenges, organizations can potentially create a better environment that fosters positive outcomes for both employees and the organization. However, the impact of occupational stress on job performance, job satisfaction and psychological distress may change over time. To address this concern, future research should test the model through a longitudinal study design.